Daily synoptic conditions associated with occurrences of compound events in estuaries along North Atlantic coastlines. (15th February 2022) - Camus, Paula; Haigh, Ivan D.; Wahl, Thomas; Nasr, Ahmed A.; Méndez, Fernando J.; Darby, Stephen E.; Nicholls, Robert J.
Abstract: Coastal compound flooding events occur when extreme events of rainfall, river discharge and sea level coincide and collectively increase water surface elevation, exacerbating flooding. The meteorological conditions that generate these events are usually low‐pressure systems that generate high winds and intense rainfall. In this study, we identify the types of synoptic atmospheric conditions that are typically associated with coastal compound events using a weather‐type approach, for the North Atlantic coastlines (encompassing northwest Europe and the east coast of the United States). Compound events are identified along the estuaries of the study region from 1980 to 2014 based on an impact function defined by water surface elevation that resulted from the combination of river discharge and sea level. We find that compound events are more frequent along European as opposed to U.S. coastlines. In both cases, they are associated with a few dominant weather patterns. European hotspots of compound events are concentrated in the west coast of United Kingdom, the northwest coast of the Iberian Peninsula and around the Strait of Gibraltar. These areas share the same weather patterns which represent the main pathways of storms that cross the North Atlantic Ocean. In the case of U.S. locations, the areas with highest number of compound events are located mainly in the Gulf of Mexico and along Mexico and along the mid‐eastern U.S. coastlines. In these areas, compound events are produced by transitional weather patterns, which describe storms that travel northward parallel to the coastline. Splitting the occurrence of compound events in the corresponding weather types discriminates the interannual variability based on the relationship with dominant climate indices in the North Atlantic Ocean. Abstract : The types of synoptic atmospheric conditions that are typically associated with compound events are identified in estuaries along the North Atlantic coastlines using a weather‐type approach. The occurrence of compound events is associated with a few dominant weather patterns usually characterized by low‐pressure systems accompanied with precipitation over the surrounding area of the site. For European coastlines, compound events are most frequent around the main pathways of the cyclone storms that cross the North Atlantic Ocean. For U.S. coastlines, locations around the Gulf of Mexico and south‐middle eastern U.S. coastlines experience the same weather patterns, which are storms that travel northward parallel to the coastline, that produce frequent compound events.